Identifikasi Senyawa Metabolit Sekunder Pada Batang dan Daun Lamun (Seagrass) di Teluk Palu - Elsa RN Taminggu; Tahril Tahril (Universitas Tadulako, 2022)
This study aims to determine the content of secondary metabolites in the stems and leaves of seagrass (Seagrass) found in Palu Bay. The method used in this study is the screening method. The samples used were stems and leaves of seagrass species Enhalus acoroides, Thalasia hemprichii, and Sringodium isotifolium. The types of compounds identified in this study were alkaloids, flavonoids, steroids, triterpenoids, saponins, and tannins. Before the qualitative test on the sample, maceration was carried out for 24 hours with ethanol as a solvent. The results obtained were the type of seagrass Enhalus acoroides, the stems contain alkaloids, flavonoids, triterpenoids, and tannins, the leaves contain alkaloids, flavonoids, steroids, saponins, and tannins. Syringodium isoetifolium seagrass contains alkaloids, titerpenoids, saponins, and tannins, the leaves contain alkaloids, steroids, and tannins. Seagrass Thalasia hemprichii contains alkaloids, flavonoids, titerpenoids, and tannins, the leaves contain alkaloids, flavonoids, steroids, and tannins. Thalasia hemprichii and Sringodium isotifolium.